Revision as of 14:44, 12 September 2008 by Johns311 (Talk)

(diff) ← Older revision | Latest revision (diff) | Newer revision → (diff)

A

Going through the system first and then the time shift:

x[n] -> y[n] = (k + 1)^2x[n-(k+1)]

y[n] -> z[n] = y[n-1]

 = (k+1)^2x[n-1-(k+1)]


Going through the time shift first and then the system:

x[n] -> y[n] = x[n-1]

y[n] -> z[n] = (k+1)^2y[n-(k+1)]

 = (k+1)^2x[n-1-(k+1)]

Since the two results are the same, the system is time invariant.


B

The input would have to be u[n]

Alumni Liaison

Basic linear algebra uncovers and clarifies very important geometry and algebra.

Dr. Paul Garrett